Xylitol Chewing Gums on the Market: Do They Prevent Caries? - Alanzi, Abrar; Soderling, Eva; Varghese, Anisha; Honkala, Eino (Oral health & preventive dentistry, 2016)
To measure the xylitol content in sugar-free chewing gums available on the market in Gulf Cooperation Council (GCC) countries in the Middle East, in order to identify those products that can provide the recommended daily dose of xylitol for caries prevention (6-7 g). Acid production from chewing gums was also measured in vitro and in vivo. Twenty-one chewing gums containing xylitol were identified and collected from the GCC market (Kuwait, Bahrain, Qatar, Saudi Arabia, UAE and Oman). Xylitol was extracted and its concentration was analysed using a special enzymatic kit. The pH of extracts was measured during 30-min incubation with Streptococcus mutans. Changes in saliva and plaque pH were noted in four subjects after the consumption of highly concentrated xylitol gums. The xylitol content in grams was clearly mentioned only on one product's label. Twelve products stated the percentage of xylitol (3.5% to 35%). The rest did not specify the amount. The mean measured weight of one piece of gum was 1.67 ± 0.38 g. The mean measured xylitol content/piece was 0.33 ± 0.21 g. Xylitol content was < 0.3 g/ piece in 9 products, 0.3-0.5 g in 7 and > 0.5 g in 5 products. None of the highly concentrated xylitol gums showed a pH drop in vitro or in vivo. One chewing gum, containing xylitol and glucose, resulted in a low pH level (< 5.5) when tested in vitro. The majority of xylitol chewing gums sold on the GCC market do not provide the consumers with the recommended daily dose of xylitol for caries prevention. Clear, accurate labeling is recommended.